The Gaps of Urban Governance: Questionings and Perceptions upon Metropolitan Lisbon Urban Management - Seixas, João (2002)
Given the current political and institutional crossroads of the metropolis of Lisbon, there is a need for new (and urgent) approaches, as well as corresponding actions. The understanding of these approaches calls for a dynamic perspective, in the understanding and management before the perceptions and the strategies of the different actors, and the consequent processes of urban change. From this perspective, an inductive research is suggested, questioning the actors on the main urban governance challenges that arise, after an analysis of the metropolitan challenges themselves. A corresponding critical analysis seeks to clarify the main areas of reflection, and suggests levels for further research.